IMPLEMENTASI GAYA DAN TEMA KONTEKSTUAL DALAM PERANCANGAN INTERIOR ERA PASCA MODERN - Aghastya Wiyoso (Jurnal Dimensi Seni Rupa dan Desain, 2007)
AbstractDesign is still growing relatively as a new discipline. Now Design has already left its old paradigm, as an ornament embellishment of the product or space, to gain a new responsibility to solve advanced and complex needs of humankind behind a designed object. This change, also in the field of inten~or design, acted its design process which must combine both aesthetical and rational ability. Design concept, included a theme in it, is one important step of the design process and play a role as a problem solving anticipation that can direct the whole design process to the right goal or criteria which already stated in early phase. Styles must response physically the theme establls"lzed before. In the age of pluralism with a more complex growlh of space categories and thetr~ requirements, determim'ng themes creatively and recombim"ng and recontextualizing styles are needed to achieve a close relationship between space structures and their meam'ng or content.Ke ywords . design, interior design, design concept, implementation theme and style AbstrakDesain kini terus berkembang sebagai disiplin ilmu yang relatif baru. Hingga saat ini desain telah meninggalkan paradigma lama sebagai suatu penghias dan ruang atau produk untuk memperoleh suatu peran baru, yaitu memecahkan masalah kebutuhan manusia yang kian kompleks yang berada di bank suatu obyek desain. Perubahan ini juga terasa dalam desain interior, pengaruhnya pada proses desain mengkombinasikan kepekaan  estetis dan kemampuan rasional. Konsep desain, termasuk didalamnya tema merupakan salah satu langkah penting dalam proses desain dan memainkan peran sebagai antisipasi pemecahan masalah yang dapat mengarahkan keseluruh